Phenotypic Characterization of Polysaccharidases Produced by Four Prevotella Type Strains - Hiroki Matsui; Koretsugu Ogata; Kiyoshi Tajima; Mutsumi Nakamura; Takafumi Nagamine; Rustam I. Aminov; Yoshimi Benno (Current Microbiology, 2000)

Desulfotomaculum genus‐ and subgenus‐specific 16S rRNA hybridization probes for environmental studies - Krassimira R. Hristova; Margit Mau; Dandan Zheng; Rustam I. Aminov; Roderick I. Mackie; H. Rex Gaskins; Lutgarde Raskin (Environmental Microbiology, 2000)
Based on comparative analysis of 16S rRNA sequences and the recently established phylogeny of the genus Desulfotomaculum , a set of phylogenetically nested hybridization probes was developed and characterized. A genus‐specific probe targets all known Desulfotomaculum species (with the exception of Desulfotomaculum acetoxidans ), and five specific probes target subclusters within the Desulfotomaculum genus. The dissociation temperature of each probe was determined experimentally. Probe specificities were verified through hybridizations with pure culture rRNA isolated from a wide variety of target and non‐target organisms and through an evaluation of probe ‘nesting’ using samples obtained from four different environments. Fixation and hybridization conditions for fluorescence in situ hybridizations were also optimized. The probes were used in quantitative membrane hybridizations to determine the abundance of Desulfotomaculum species in thermophilic anaerobic digesters, in soil, in human faeces and in pig colon samples. Desulfotomaculum rRNA accounted for 0.3–2.1% of the total rRNA in the digesters, 2.6–6.6% in soil, 1.5–3.3% in human faeces and 2.5–6.2% in pig colon samples.